A study on turnover intention among banks' employees in Kuching - Bong, Wei Chen (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The purpose of this research is to study the banks' employee perception on the turnover intention in banking industry in Kuching, Sarawak. Questionnaire has been distributed,to banks employees in few commercial banks in Kuching. Results of questionnaire with . 63 samples of banks' employee indicated that organizational commitment and organizational justice have highly significant to job satisfaction level in their workPla1 It was found that banks' employee who meet job satisfaction will commit to its organization and agreed with the organization decision. Also, there are weak significant relationships between job satisfaction levels to bank employee's turnover intention. It was also found that Kuching banks employee who meet high job satisfaction also will intent to leave the bank. Descriptive analysis, reliability analysis, Pearson correlation and regression analysis were used in this study. In addition, limitation of the research and some recommendations for future research were made.